2021
DOI: 10.1136/sextrans-2020-054851
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviours associated with incident high-risk anal human papillomavirus among gay and bisexual men

Abstract: ObjectiveHigh-risk human papillomavirus (HRHPV) causes anal cancer, which disproportionately affects gay and bisexual men (GBM). We examined sexual behaviours associated with incident anal HRHPV in an observational cohort study of GBM in Sydney, Australia.MethodsGBM aged 35 years and above were enrolled in the Study of the Prevention of Anal Cancer. Detailed information on sexual practices in the last 6 months, including receptive anal intercourse (RAI) and non-intercourse receptive anal practices, was collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Anal swab samples were tested using Seegene Anyplex II HPV28 (Anyplex28; Seegene, Seoul, South Korea) as described previously ( 10 , 42 44 ). The Anyplex28 assay detects 28 HPV genotypes being deemed as HR (16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 66, and 68) or potential HR and low-risk (6, 11, 26, 40, 42, 43, 44, 53, 54, 61, 69, 70, 73, and 82).…”
Section: Methodsmentioning
confidence: 99%
“…Anal swab samples were tested using Seegene Anyplex II HPV28 (Anyplex28; Seegene, Seoul, South Korea) as described previously ( 10 , 42 44 ). The Anyplex28 assay detects 28 HPV genotypes being deemed as HR (16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 66, and 68) or potential HR and low-risk (6, 11, 26, 40, 42, 43, 44, 53, 54, 61, 69, 70, 73, and 82).…”
Section: Methodsmentioning
confidence: 99%
“…Besides HIV, gay people are more vulnerable to other diseases related to receptive anal intercourse, which can be less common in the general population. The stratified analysis suggests that receptive anal intercourse has the primary role in anal HPV transmission, and the use of a condom does not have protective effects against high-risk HPV [3]. Thus, gay people are often exposed more to HPV and anal cancer.…”
Section: Policies Should Cater the Needs Of The Lgbtq+ Groupmentioning
confidence: 99%
“…79 In MSM, it has been shown that condomless receptive anal intercourse and increased number of partners in the last 6 months has been associated with elevated risk of anal HPV infection. 94 A recent systematic review and meta-analysis have demonstrated incidence rates for anal cancer based on risk group. 2 Persons LWH are especially vulnerable to the dysplastic effects of HPV infection, and among MSM LWH, the highest risk group, the incidence of anal cancer was 85 per 100,000 persons, with even higher risks in older MSM LWH when stratified by age.…”
Section: Analmentioning
confidence: 99%